Age at first alcohol use and weapon carrying among adolescents: Findings from the 2019 Youth Risk Behavior Survey. (September 2021) - Baiden, Philip; Jahan, Nusrat; Onyeaka, Henry K.; Thrasher, Shawndaya; Tadeo, Savarra; Findley, Erin
Abstract: Background: Although studies have investigated the association between alcohol use and violent behaviors such as weapon carrying, few studies have examined the association between age at first alcohol use and weapon-carrying among adolescents. The objective of this study was to investigate the association between age at first alcohol use and weapon carrying among adolescents. Methods: Data for this study came from the 2019 Youth Risk Behavior Survey. An analytic sample of 13, 442 adolescents aged 14–18 years old (51% female) was analyzed using binary logistic regression. The outcome variable investigated in this study was weapon carrying during the past 30 days, and the main explanatory variable investigated was age at first alcohol use. Results: Of the 13, 442 adolescents, 13.5% carried a weapon during the past 30 days, and 15.4% reported having their first alcoholic drink before age 13. In the multivariable logistic regression, adolescents who reported having alcohol before age 13 had more than double the odds of carrying a weapon when compared to those who never had alcohol before age 13 (AOR = 2.32, p < .001, 95% CI = 1.87-2.89). Other significant factors associated with weapon carrying include male gender, victim of bullying, teen dating violence, sexual violence, suicidal ideation, and history of substance use. Adolescents who self-identified as Black/African American or Hispanic were significantly less likely to carry a weapon when compared to adolescents who self-identified as non-Hispanic White. Conclusion: The findings of this study underscore the importance of developing age appropriate intervention strategies to curb early initiation of alcohol use and weapon carrying among adolescents. Highlights: Adolescents alcohol use and weapon carrying are major public health concerns in the United States. About 13.5% of adolescents carried a weapon during the past 30 days. About 15.4% of adolescents reported having their first alcoholic drink before age 13. Adolescents who had their first alcohol before age 13 had more than double the odds of carrying a weapon.